ANALYSIS OF FOREST FIRE CASES USING GSTAR(1;1) MODEL WITH SPATIAL ROOK CONTIGUITY WEIGHTS MATRIX IN WEST KALIMANTAN - Muhammad Yahya Ayyash; Nur'ainul Miftahul Huda; Nurfitri Imro'ah; Hesty Pratiwi (Jurnal Matematika UNAND, 2026)
In West Kalimantan, forest and land fires cause damage to ecosystems, the loss of biodiversity, and detrimental repercussions on both health and the local econ- omy. Extreme weather and land clearance for agricultural and plantation purposes are the primary reasons. This study aims to investigate forest firesâ€™ spatial and temporal pat- terns by employing the Generalized Space-Time Autoregressive (GSTAR)(1;1) approach with spatial rook contiguity weights. From January 2020 to March 2024, the data used consisted of the number of monthly forest fires that occurred in the Ketapang, Sanggau, Sintang, Landak, and Sekadau Regencies. According to the findings, the spatial pattern demonstrates strong interactions between regions in which flames in one area affect fires in other locations. The temporal pattern demonstrates that prior fires can impact firesÂ that occur in the subsequent period, depending on the area. The model has an aver- age accuracy level of 13%, which indicates that this model has a reasonable degree of accuracy that can be used for making predictions. This study concluded that a better understanding of the spatial-temporal patterns of forest fires can improve early warning systems and rapid responses to probable future fires.